1988
DOI: 10.2307/1941020
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Limitation and Metrosideros Forest Dieback in Hawaii

Abstract: Large numbers of Metrosideros polymorpha trees have died in the montane rain forest on the Island of Hawai'i, but previous research has failed to identify a principal cause. This paper describes an experiment that tests the hypothesis that nutrient deficiency is the principal cause of tree death and stand—level dieback. Treatments were fertilizing, stand thinning, and a combination of the two. No significant change in the mortality rate was caused by the treatments; however, stem diameter growth of surviving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 8 publications
0
25
1
Order By: Relevance
“…In other studies, Tanner et al (1990) demonstrated that N and P additions increased tree growth in unreplicated Jamaican montane forest plots, and Gerrish et al (1988) reported that a complete fertilizer increased tree growth in two Hawaiian montane forests. Within stands, Cuevas & Medina (1988) demonstrated that tree roots in an Amazonian forest on an oxisol responded to spot additions of P and Ca (but not N) with increased growth, while those in a forest on a spodosol responded to added N, these results were consistent with the observed C:nutrient ratios in tissue and concentrations in soils in those sites (Cuevas & Medina 1986;Medina & Cuevas 1989).…”
Section: Introductionmentioning
confidence: 91%
“…In other studies, Tanner et al (1990) demonstrated that N and P additions increased tree growth in unreplicated Jamaican montane forest plots, and Gerrish et al (1988) reported that a complete fertilizer increased tree growth in two Hawaiian montane forests. Within stands, Cuevas & Medina (1988) demonstrated that tree roots in an Amazonian forest on an oxisol responded to spot additions of P and Ca (but not N) with increased growth, while those in a forest on a spodosol responded to added N, these results were consistent with the observed C:nutrient ratios in tissue and concentrations in soils in those sites (Cuevas & Medina 1986;Medina & Cuevas 1989).…”
Section: Introductionmentioning
confidence: 91%
“…Metrosideros dieback does not affect saplings or vigorously growing young trees. No acute strees or biotic agent has been found to be the primary cause of dieback, nor is acute deficiency of inorganic nutrients responsible for dieback in mature, closed canopy forests (Gerrish et al 1988). Regeneration of Metrosideros usually follows canopy breakdown and leads to the establishment of another cohort of the same species.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of studies within Metrosideros dieback areas on younger substrates (Gerrish et al 1988), there has been little previous work on mortality rates of Metrosideros trees greater than sapling size in Hawaii. Burton and Mueller -Dombois (1984) found high mortality (57%/yr) for Metrosideros seedlings growing in < 5% irradiance, but that annual mortality decreased to 13% for seedlings growing at > 5% irradiance.…”
Section: Discussionmentioning
confidence: 99%